1998
DOI: 10.1007/s002689900471
|View full text |Cite
|
Sign up to set email alerts
|

l‐Arginine: Effect on Reperfusion Injury after Heart Transplantation

Abstract: Global myocardial ischemia and reperfusion injury play a major role in early postoperative myocardial graft dysfunction. The aim of the present study was to investigate the effects of the nitric oxide (NO) precursor L-arginine on myocardial and endothelial function after hypothermic ischemia and reperfusion in a heterotopic rat heart transplantation model. After 1 hour ischemic preservation, reperfusion was started after application of placebo (control, n = 12) or L-arginine (L-Arg 40 mg/kg, n = 12), a substra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 40 publications
2
18
0
Order By: Relevance
“…On the other hand, the control group showed a recovery after 24 hours with similar values to the PJ34 group, suggesting that that the applied cardiac preservation time and reperfusion lead to only reversible changes of functional status of the heart. 16,17 Although no differences were found between the groups in systolic and diastolic function and baseline coronary blood flow after 24 hours of reperfusion, endothelial function was still depressed in the control group as indicated by the lower CBF response to acetylcholine and bradykinin. The fact that after 24 hours reperfusion the histological specimens from both control and PJ34 showed only little PARP activation suggested that delayed endothelial dysfunction in the control animals may be a late consequence of a transient, earlier burst of PARP activation and subsequent cellular alterations.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…On the other hand, the control group showed a recovery after 24 hours with similar values to the PJ34 group, suggesting that that the applied cardiac preservation time and reperfusion lead to only reversible changes of functional status of the heart. 16,17 Although no differences were found between the groups in systolic and diastolic function and baseline coronary blood flow after 24 hours of reperfusion, endothelial function was still depressed in the control group as indicated by the lower CBF response to acetylcholine and bradykinin. The fact that after 24 hours reperfusion the histological specimens from both control and PJ34 showed only little PARP activation suggested that delayed endothelial dysfunction in the control animals may be a late consequence of a transient, earlier burst of PARP activation and subsequent cellular alterations.…”
Section: Discussionmentioning
confidence: 95%
“…16,17,27,30,31 Summarizing the data of these studies, a biphasic recovery pattern is characteristic for this model with an early phase (Ͻ1 hour) followed by a further improvement during the next 24 hours. Furthermore, different agents such as adenosine, 30 endothelin receptor antagonists, 17 the NOprecursor L-arginine, 16 the NO-donor SIN-1 (unpublished data), and free radical scavengers 31 effectively reduced reperfusion injury. Taking into account that in some of the studies ischemic time 30,31 or assessment protocol 30 was different, PARP inhibition seems to be an effective therapeutic modality for reducing reperfusion injury in comparison to other, previously tested agents.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our laboratory, we previously showed in canine orthotopic heart transplantation [37] and cardiopulmonary bypass models of global ischemia/reperfusion [38] and in a rat model of transplantation-induced ischemia/reperfusion injury [14] decreased LV contractility. However, we and others have already demonstrated that 24 h after transplantation systolic and diastolic function return to normal [39,40]. In the present study persistence of graft dysfunction 24 h after transplantation needs to be considered during heart transplantation when hearts from donor with alcohol abuse are used.…”
Section: Discussionmentioning
confidence: 94%